1970
DOI: 10.1079/bjn19700018
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the microbiology and biochemistry of the rumen in cattle given different quantities of a pelleted barley ration

Abstract: I. Three heifers were changed from a diet of equal parts of hay and barley cubes (50:~o diet) to one entirely of barley cubes given in three equal feeds throughout the day. Feed intake was restricted to 80 % of calculated appetite at the time of change and this percentage progressively decreased as the live weights of the animals increased.2. The change of diet had no significant effect on the volume of rumen fluid but the rate of outflow from the rumen was significantly lower on the barley diet than on the 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 27 publications
12
44
3
Order By: Relevance
“…The increased butyrate proportion of the VFA mixture in the faunated sheep, at the expense of propionate and valerate, is consistent with previously published results (Jouany et al, 1988). This trend was less marked in Isotricha-monoinoculated sheep than in mixed-faunated sheep, and is probably the direct consequence of butyrate production by the entodiniomorphid ciliates (Eadie et al, 1970). On the other hand, the lactate that could be produced with such diets was never detected in the sheep rumen juice throughout the experiment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased butyrate proportion of the VFA mixture in the faunated sheep, at the expense of propionate and valerate, is consistent with previously published results (Jouany et al, 1988). This trend was less marked in Isotricha-monoinoculated sheep than in mixed-faunated sheep, and is probably the direct consequence of butyrate production by the entodiniomorphid ciliates (Eadie et al, 1970). On the other hand, the lactate that could be produced with such diets was never detected in the sheep rumen juice throughout the experiment.…”
Section: Discussionsupporting
confidence: 91%
“…It is generally accepted that highly acidic pH values in the rumen can inhibit the growth of ciliates (Purser and Moir, 1959) and may even cause their complete elimination (Eadie et al, 1970;Whitelaw et al, 1972;Rung et al, 1986). The decline in the number of entodiniomorphid ciliates noted here during the 3 h following the meal in the rumen juice was always observed in the numerous experiments we carried out.…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, in absence of increased mobilization of adipose tissues, as suggested by measured plasma NEFA concentrations and the calculated energy balance, the higher plasma BHBA concentrations likely arise from increased butyrate absorption and conversion to BHBA in the rumen wall (Kristensen et al, 2000). Because animals were fed every 3 h at restricted intake levels, the possibility of a subacute butyric acidosis associated with starch diets (Eadie et al, 1970) should be considered here. Results from the aforementioned metabolic trial (Cantalapiedra-Hijar et al, 2013) confirmed an almost twofold higher butyrate net portal absorption for starch compared with fiber diets.…”
Section: Discussionmentioning
confidence: 99%
“…Which species of bacteria increased in its number according to the decrease in protozoal number was not shown in that report. However increase of starch digesting bacteria by the defaunation was reported13) and EADIE et al 6) also observed that the increase in the number of Bacteroides-type rods and Selenomonas ruminantium was associated with the reduction in protozoal number. Those groups of bacteria produce mainly propionic acid or its precursors.…”
Section: Resultsmentioning
confidence: 91%